The veiled kingdom - Renee, Holly (Renee, Holly, Veiled Kingdom series, 2024)
Fleeing my father's cruelty, the wicked king who robbed me of a future, I face death in the streets, caught between a rebellion and a tyrant's reign. Captured by those sworn to kill me, the rebels remain blind to my true identity, the missing daughter of the despised king. Faced with an impossible choice, I stand before them: join the rebels or face their blades. Yet, Dacre, the son of the ruthless rebellion commander, becomes torn between suspicion and a desire that mirrors my own. He allows no one to touch me, tries to protect me, yet threatens me at every turn. As secrets are weaved beyond our hidden realm, a fierce battle unfolds within me. As I get closer to the rebels, and their cause, my loyalty to my kingdom clashes with my undeniable devotion to Dacre and the burning connection between us. In a world where love and hate are two edges of the same blade, I find myself caught in a delicate dance between forbidden desire and my looming destiny.--Publisher description.